Local and regional drivers influence how aquatic community diversity, resistance and resilience vary in response to drying. Issue 12 (22nd September 2020) - Sarremejane, Romain; England, Judy; Sefton, Catherine E. M.; Parry, Simon; Eastman, Michael; Stubbington, Rachel
Abstract : Disturbance events govern how the biodiversity of ecological communities varies in both space and time. In freshwater ecosystems, there is evidence that local and regional‐scale drivers interact to influence ecological responses to drying disturbances. However, most research provides temporal snapshots at the local scale, whereas few studies encompass a gradient of drying severity spanning multiple years. Using a dataset of rare spatiotemporal extent and detail, we demonstrate how independent and interacting local and regional‐scale factors drive shifts in the α and β diversities of communities in dynamic river ecosystems. We examined aquatic invertebrate assemblage responses to hydrological variability (as characterized by monthly observations of instream conditions) at 30 sites over a 12‐year period encompassing typical years and two severe drought disturbances. Sites varied in their disturbance regimes and hydrological connectivity at both local (i.e. site‐specific) and regional (i.e. river catchment) scales. Whereas α diversity was mainly influenced by local factors including flow permanence and the temporal extent of ponded and dry conditions, both temporal and spatial β diversities also responded to regional‐scale metrics such as the spatial extent of flow and hydrological connectivity. We observed stronger local negative responses for taxa with lower capacities to tolerate drying (i.e. resistance) and/or to recover after flow resumes (i.e. resilience), whereas taxa with functional traits promoting resilience made an increasing contribution to spatial β diversity as hydrological connectivity declined. As droughts increase in extent and severity across global regions, our findings highlight the functional basis of taxonomic responses to disturbance and connectivity, and thus advance understanding of how drying disturbances shape biodiversity in river networks. Our identification of the role of regional hydrological factors could inform catchment‐scale management strategies that support ecosystem resilience in a context of global change.